Intrasaccular flow-diversion for treatment of intracranial aneurysms: the Woven EndoBridge. (May 2014) - Mine, Benjamin; Pierot, Laurent; Lubicz, Boris
Abstract : Endovascular approach is now the first option for the treatment of most intracranial aneurysms (IA). However, remaining limitations are the suboptimal stability of aneurysm occlusion and the treatment of complex IA. The use of conventional and flow diverter stents has partially addressed these limitations. Nevertheless, as intraluminal devices, stents require aggressive antiplatelet therapy and are associated with higher thromboembolic (TE) complication rates. Intrasaccular flow disrupters (IFD) are newly developed braided-wire devices designed to achieve flow disruption at the neck without placing material in the parent vessel and without the need of antiplatelet therapy. First clinical series have shown promising anatomical and clinical results. Our purpose is to describe the available IFD and to review the literature about their efficacy, safety, limitations, and developments.